DESIGN OF A PORTABLE DIGITAL SCOLIOMETER BASED ON A MICROCONTROLLER FOR EARLY DETECTION OF SCOLIOSIS - Firman Nur Hidayat; Bagus Adhi Kusuma (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Scoliosis is a spinal disorder that is often not detected early, potentially causing postural disorders and more serious complications. Early detection through the measurement of Angle of Trunk Rotation (ATR) using conventional scoliometers still has limitations in terms of portability and reading subjectivity. This study aims to design and build a portable microcontroller-based digital scoliometer capable of measuring ATR values in real-time. The developed system uses an MPU6050 sensor to read body tilt angle, processed with the Kalman Filter method to improve data stability, and an ESP32 microcontroller for data processing and transmission to a web-based system via WiFi protocol. Testing was performed experimentally covering component functionality tests, ATR angle reading tests, and data transmission tests. The test results show that the device can measure ATR values stably at various tilt positions, display data in real-time on an LCD, and successfully transmit 8 out of 10 measurement data to the web server without delay. 2 transmissions experienced 4-second and 10-second delay caused by network instability. Overall, the developed digital scoliometer is proven to function as a practical, portable, and digitally-based scoliosis early detection tool.